2019
DOI: 10.1007/s42452-019-0818-4
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic synthesis of silver nanoparticles using Priva cordifolia leaf extract (PC@AgNPs) a potent antioxidant, antibacterial and catalytic activity

Abstract: A nanoparticle preparation (PC@AgNPs), synthesized biogenically using Priva cordifolia leaf extract was found to possess quenching property of stable DPPH and ABTS in dose dependent manner. The PC@AgNPs showed well-established physicochemical stability with respect to temperature, P H and salinity. It showed a broad bactericidal effect against 10 pathogenic bacteria, notably Staphylococcus aureus, Escherichia coli, Shigella flexneri and Vibrio parahaemolyticus. Its non-toxicity up to 500 µg mL −1 concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Biological methods involve simple bioreduction methods and need not separate capping processes and separate capping agents. AgNPs have been prepared using different plant extracts including Gymnema sylvestre [36], Centella asiatica [37], Melia dubia [38], Rhynchosia suaveolens [39], Shorea roxburghii [40], Morus alba [41], Priva cordifolia [42], Catharanthus roseus [43], Andrographis paniculata [44], Cordia dichotoma [45], Cassia angustifolia [46], Amaranthus cruentus [47], Cola nitida [48], Arnebia hispidissima [49], Petiveria alliacea [50], Persea Americana [51], Buchanania axillaris [52], and Jatropha curcas [53] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Biological methods involve simple bioreduction methods and need not separate capping processes and separate capping agents. AgNPs have been prepared using different plant extracts including Gymnema sylvestre [36], Centella asiatica [37], Melia dubia [38], Rhynchosia suaveolens [39], Shorea roxburghii [40], Morus alba [41], Priva cordifolia [42], Catharanthus roseus [43], Andrographis paniculata [44], Cordia dichotoma [45], Cassia angustifolia [46], Amaranthus cruentus [47], Cola nitida [48], Arnebia hispidissima [49], Petiveria alliacea [50], Persea Americana [51], Buchanania axillaris [52], and Jatropha curcas [53] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Phytosynthesis of AgNPs is a bottom-up approach involving the reduction and oxidation reactions mediated by enzymes, proteins, flavonoids, polyphenols or other biomolecules with reducing properties. AgNPs have been synthesized successfully using different plant extracts including Salvinia molesta [3], Berberis vulgaris [12], Olax scandens [13], Punica granatum [19], Convolvulus arvensis [21], Morus alba [23], Tithonia diversifolia [24], Bauhinia acuminate [25], Phlomis bracteosa [26], Tanacetum vulgare [27], Ficus religiosa [28], Mangifera indica [29], Nyctanthes arbor [30], Priva cordifolia [31], Artocarpus heterophyllus [32].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the biosynthesis of metal nanoparticles (MNPs) have been proposed as a cost-effective and eco-friendly substitute to chemical methods. Many studies have been demonstrated the biosynthesis of AgNPs mediated by the microorganism or by phytochemicals or enzymatic synthesis [11,18,19,[29][30][31][32][33]. Among the biological methods, photosynthesis which involves reduction by phytochemicals derived from plants seems to be the superior choice.…”
Section: Introductionmentioning
confidence: 99%